Strategie skandalu i stereotypy odbioru - Michałowski, Piotr (Przestrzenie Teorii, 2007)
The terms used in this title are connected - as two opposite kinds of reaction to the text and they exist outside: in conciousness of author and reader. Stereotype is necessary to hold intercourse; scandal is the effect of disturbance in communication but sometimes there is inversely: the communication bases on expectation of scandal - as particular convention. Scandal is a subjective phenomenon; it isn't an event, but it is a kind of response: protest or indignation. Most often it is created by media. This article is also the attempt formulate a small theory of scandal. It diferentiates accidental scandal from specially prepared one. Each of them is possible only it concerns the context of: person's life (1), point of view (2), custom (3) or artistic canon (4). In the first one scandal is connected with a message; in the rest - depends only on verbal act.